Immunohistochemical and quantitative analysis of ghrelin in Syzygium aromaticum - Aydin, Suleyman; Dagli, Adile F.; Ozkan, Yusuf; Kendir, Yalcin; Sahin, Ibrahim; Aksoy, Aziz; Ozercan, Ibrahim H. (Portland Press Ltd, 2011)
Ghrelin, an endogenous ligand of the growth hormone secretagogue receptor, has been identified in mammals, fish, amphibians, birds, reptiles and some plants. The present investigation was designed to determine whether ghrelin is present in the appetite-stimulating plants Syzygium aromaticum and Salvadora persica, using IHC (immunohistochemistry) to indicate the location of the peptide and ELISA to measure the concentration. ELISA demonstrated that a ghrelin-like substance was present at concentrations of 4070.75 +/- 664.67 and 75.25 +/- 24.49 pg/mg in the tissues of flower bud of S. aromaticum and branch of S. persica, respectively. The concentration of ghrelin in human salivary gland tissue was 436.00 +/- 95.83 pg/mg. Ghrelin was predominantly localized to the T (trachea) and PCs (parenchyma cells) in the flower bud of S. aromaticum. However, no ghrelin immunoreactivity was observed in the PC or T of the branch of S. persica. The evolutionary role of this peptide hormone in plants and animals suggests that they have evolved in a more similar way than previously thought.
Keywords: ghrelin; immunohistochemistry; plant; Syzygium aromaticum